COMPETENCY BASED CURRICULUM PREPAREDNESS: PERCEPTION OF TEACHERS IN SELECTED PUBLIC AND PRIVATE PRIMARY SCHOOLS IN KENYA - Koros, Dr. Peter; Achieng, Sr. Dr.Madeleine Sophie Barat (IJRDO- Journal of Educational Research, 2023)
The purpose of the study was to establish teachers’ perception on their preparedness to implement the Competency Based Curriculum (CBC) in public and private primary schools in Kenya. CBC was rolled out by the Kenya Institute of Curriculum Development in January 2018 and since then, studies have indicated that teachers who are the key implementers of the curriculum are not adequately trained. The current study sought to establish teachers’ perception on their preparedness to implement the Competency Based Curriculum in selected public and private primary schools in Kenya. The study was anchored on instructional design theory and targeted 23,286 public primary schools and 9,058 private primary schools in Kenya. The actual sample was made of 19 public primary schools and 31 private primary schools. The study adopted a convergent parallel mixed methods research design using a cross sectional survey design for the quantitative method and phenomenological design for the qualitative method. Data were collected using questionnaires and focus group discussions. Descriptive and inferential statistics were generated using MS Excel 2020 and SPSS version 21. Qualitative data from the focus group discussions were analyzed thematically and report given in narrative form and direct quotes. The findings revealed among other factors that digital literacy is still a challenge among teachers and that the number of trained teachers in the selected schools was approaching expectation. Resources for CBC are there in a number of schools but quite inadequate in a number of public schools. The study recommended that the training of teachers at all levels should be on-going and that there is an urgent need to help teachers understand the use of CBC assessment rubrics.